Distribution, characteristics, and human exposure to microplastics in mangroves within the Guangdong-Hong Kong-Macao Greater Bay Area. (February 2022) - Yu, Lingyun; Li, Ruili; Zhang, Zhi; Wu, Hailun; Chai, Minwei; Zhu, Xiaoshan; Guo, Wenxiao
Abstract: In this study, three mangroves in the Guangdong-Hong Kong-Macao Greater Bay Area— Qi'ao Island in Zhuhai, Nansha in Guangzhou, and Futian in Shenzhen—were selected for investigating the distribution of microplastics and their characteristics The average microplastic abundance in each descended in the order: Futian (1600 n/kg) > Nansha (1100 n/kg) > Qi'ao Island (440 n/kg), with values from the forest fringe being significantly higher than those in the forest interior. The microplastics were mainly fibers, 1–5 mm in size, and white/black in color; they consisted of polypropylene and polyethylene, with foam and polystyrene accounting for a high proportion in Nansha. The exposure of humans to microplastics in the Futian forest fringe reached 35.95 ng/d·kg; it was one order of magnitude higher than the exposures in Qi'ao Island and Nansha. Furthermore, ingestion accounted for approximately 74% of the total exposure to the human body, dermal contact constitutes 25%, and sediment inhalation accounted for less than 1%. Highlights: The average MP abundance in mangrove was Futian > Nansha > Qi'ao Island. The MP abundance in forest fringe was higher than that in forest interior. The MPs were featured with fiber shape, 1–5 mm size, white/black color and PP/PE. The MPs in FT-FR had the highest human exposure of 35.95 ng/d·kg. Ingestion accounted for most of MP exposure, followed by dermal contact and inhalation.